ANALYSIS OF PUBLIC PERCEPTION OF HALAL LABELING ON NON-FOOD HALAL PRODUCTS IN BANDUNG CITY - Bishri, Musthafa Hasan; Muhibah, Iis (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
This study aims to determine clearly and based on scientific indication how people's perceptions of labeling non-food products, whether they agree or disagree, are essential. Then also to find out what factors influence these perceptions. The method used in this research is descriptive analysis with a quantitative approach. Based on the conclusions of this study, as many as 86% of the people of Bandung City said they "agreed" with halal labeling on non-food products. Then another 14% said they disagreed with halal labeling on non-food products. As for the important perception, as many as 73.7% of the people of Bandung City said it was "important" to halal labeling on non-food products. Then another 26.3% stated that halal labeling on non-food products is unimportant. At the same time, the factors that induce these perceptions are significantly induced by factors of education level, age, income, understanding, access to information media, and experience. Keywords: Halal Labeling, Perception, Halal Product